Kolb's Learning Styles of Centennial Stakeholders as Part of Transition Design Approach in the Social Laboratory Framework - Mellink-Méndez, Sialia Karina; Murillo-Aviña, Gloria Janeth; Chapela-Cerecero, José Esteban; López-Leyva, Josué Aarón (My University, 2025)
Wicked problems are related by many interdependent factors making them seem impossible to solve. Some examples of wicked problems are education models, health care, income disparity, poverty, financial crises, and sustainability, among others. The analysis of wicked problems requires considering many aspects involved, in particular, the level and quality of stakeholder participation. If the stakeholders do not collaborate, it will not be possible to describe the wicked problem in depth, much less propose solutions. To explore the relationship with Centennial stakeholders, this research presents an exploratory, crosssectional, and quantitative analysis of learning styles according to Kolb's theory for Centennial stakeholders in a Transition Design approach. The results show that there are some predominant learning styles, e.g., Accommodation (LS1) related to feeling and doing, and Diverging (LS3) related to feeling and watching. Then, these learning styles are related to the various practices developed in the Transition Design approach. The conceptual and methodological contribution of the research is also presented, as well as the managerial and policy implications in the framework of a social laboratory. Finally, it is concluded that, according to our survey, Centennial stakeholders have a balance regarding learning styles that must be considered as part of the design of the approach to wicked problems.
iafor Research Archive
Keywords: Community & society; Education; Sustainability & society; Social Justice; Development & political movements; Campus Ensenada